The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10802-009-9329-x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Predictors of Desistance and Level of Persistence in Offending in Early Onset Offenders

Abstract: Childhood predictors of adolescent offending careers were studied in 310 boys from the longitudinal Pittsburgh Youth Study who started offending prior to age 12. Three main groups were distinguished: serious persisters (n=95), moderately serious persisters (n=117), desisters (n= 63), and an intermittent group (n=35). Group membership was predicted using risk and promotive factors measured in childhood. Serious and moderately serious persisters could be distinguished well from desisters (29.2% and 32.3% explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
16

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 44 publications
4
36
0
16
Order By: Relevance
“…In addition, stable marital relationships and family social bonds may predict desistance in adulthood (Sampson & Laub, 1993). Desisters also report stronger, more positive family relationships than their persistent counterparts (van Domburgh, Loeber, Bezemer, Stallings, & Stouthamer-Loeber, 2009). Social capital derived from family connections may explain the positive effects of family ties (Farrall & Calverley, 2006).…”
mentioning
confidence: 94%
“…In addition, stable marital relationships and family social bonds may predict desistance in adulthood (Sampson & Laub, 1993). Desisters also report stronger, more positive family relationships than their persistent counterparts (van Domburgh, Loeber, Bezemer, Stallings, & Stouthamer-Loeber, 2009). Social capital derived from family connections may explain the positive effects of family ties (Farrall & Calverley, 2006).…”
mentioning
confidence: 94%
“…A este nível, destacam-se dois argumentos-chave empiricamente validados. Em primeiro lugar, o comportamento delinquente persistente tende a iniciar durante a infância (Le Blanc & Fréchette, 1989;Kazemian & Farrington, 2005;Moffitt, 1993;Van Domburgh, Loeber, Bezemer, Stallings, & Stouthamer-Loeber, 2009). Nesta linha de análise, vários autores propõem trajetórias-tipo em que a persistência de comportamentos delinquentes é geralmente definida pela sua precocidade e estabilidade ao longo da vida (Andersson et al, 2012;Fréchette & Le Blanc, 1987;Moffitt, 1993Moffitt, , 2006 …”
Section: Revista De Psicologíaunclassified
“…Através de um desenho longitudinal seria ainda possível avaliar diferentes tipos de percursos de reincidência, considerando a evolução, a severidade e o tipo de crimes praticados (cf. Mulder et al, 2012;Van Domburgh et al, 2009). Também a constituição da amostra pode ser apontada como limitação, na medida em que não é representativa do universo de jovens com medida tutelar educativa em Portugal.…”
Section: Conclusãounclassified
See 1 more Smart Citation
“…Among children with CP, those whose antisocial behaviour persists display more aggressive behaviour. 20,21 While some studies suggest that instrumental aggression is the precursor of criminality, 22 others suggest that it is reactive aggression, 23 and others suggest that it is bullying. 24 Other studies of children with CP have shown that those whose antisocial behaviour is likely to persist are callous or uncaring toward others, 25,26 but among both adolescent 27 and adult offenders the alternate subtype, characterized by high levels of anxiety, is common.…”
Section: Limitationsmentioning
confidence: 99%